2018
DOI: 10.1016/j.adaj.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence screening in the dental setting

Abstract: The inclusion of brief, focused IPV interventions in dental education and the establishment of collaborations between dentists and IPV agencies for referral mechanisms, in conjunction with an overall shift in dentists' attitudes about their professional responsibilities, may facilitate IPV screening uptake in the dental setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 59 publications
(64 reference statements)
1
36
0
6
Order By: Relevance
“…A study by Parish and colleagues revealed that few dentists reported screening for interpersonal violence and felt as though it should not be a part of their professional roles. 18 Similar results have been reported among dentists regarding discussions about human papillomavirus. 19 In a study of conducted at University of Iowa College of Dentistry, 96% of dental students reported patient resistance as a perceived barrier to provide tobacco interventions.…”
Section: Discussionsupporting
confidence: 76%
“…A study by Parish and colleagues revealed that few dentists reported screening for interpersonal violence and felt as though it should not be a part of their professional roles. 18 Similar results have been reported among dentists regarding discussions about human papillomavirus. 19 In a study of conducted at University of Iowa College of Dentistry, 96% of dental students reported patient resistance as a perceived barrier to provide tobacco interventions.…”
Section: Discussionsupporting
confidence: 76%
“…In several other settings (eg, dental clinics and barber shops), screening for common health problems outside the primary care office has been shown to improve outcomes. [17][18][19] Given that nearly one-third of all dermatology patients experience some form of mental health disorder, there is an opportunity for dermatologists to incorporate routine screening into clinical practice. 20 However, depression screening is infrequently performed during visits for skin diseases, such as acne and psoriasis, that are commonly associated with mental health comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In several other settings (eg, dental clinics and barber shops), screening for common health problems outside the primary care office has been shown to improve outcomes. 17 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…In summary, in this study, we have been able to identify for the first time the relationship between TMD to exposure to IPV in women. This is particularly important as it may indicate a potential screening opportunity for individuals who present with TMD to a dental physician to explore a history of abuse, a discussion which recent literature suggests currently happens infrequently in this setting [18]. There are several, simple approaches which can be integrated into daily dental practice such as the AVDR approach; asking about abuse, validating it is not the survivor's fault, documenting and referring appropriately [19].…”
Section: Discussionmentioning
confidence: 99%
“…There are several, simple approaches which can be integrated into daily dental practice such as the AVDR approach; asking about abuse, validating it is not the survivor's fault, documenting and referring appropriately [19]. These approaches have been shown to work effectively in dental settings putting minimal strain on clinicians [18]. Further work is still required in other cohorts to identify if this relationship persists elsewhere and further work is needed to explain the pathway behind this relationship.…”
Section: Discussionmentioning
confidence: 99%